Research of modifications of a beam and signals parameterd in technological linacs - Boriskin, V.N.; Savchenko, A.N. (Вопросы атомной науки и техники, 1999)
The power current pulse linacs of electrons are used in the Science Research Complex "Accelerator" at NSC KIPT for irrradiation of materials and some products. The irrradiation sessions usually last tens of hours. Some results of the linac parameters for this period are given in the present paper.